2015
DOI: 10.1155/2015/147056
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interleukin 17A and IL17F Polymorphisms on Chronic Periodontitis Disease in Brazilian Patients

Abstract: A case-control study was conducted on patients with chronic periodontitis (CP) and healthy controls with the aim of evaluating possible association between interleukin 17A (IL17A) G197A (rs2275913) and IL17F T7488C (rs763780) polymorphisms and periodontitis. Genotypes were determined by PCR-RFLP method. Statistical analyses were conducted using the OpenEpi and SNPStas software to calculate Chi-square with Yates correction or Fisher's exact tests, odds ratios (OR), and 95% confidence intervals (CIs). SNPStas so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 71 publications
1
24
2
1
Order By: Relevance
“…IL17A AA genotype and A allele were associated with worse clinical and inflammatory periodontal parameters. IL17F polymorphisms were not associated to CP [78].…”
Section: Il17mentioning
confidence: 77%
“…IL17A AA genotype and A allele were associated with worse clinical and inflammatory periodontal parameters. IL17F polymorphisms were not associated to CP [78].…”
Section: Il17mentioning
confidence: 77%
“…After reviewing the abstracts of the 33 articles, the irrelevant studies were excluded. Finally, five eligible studies were included in the meta‐analysis . Our case‐control results were added to the pooled data.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, five eligible studies were included in the meta-analysis. [9][10][11]17,18 Our case-control results were added to the pooled data. The study-selection procedure is shown in Figure . Elementary data, including the name of the first author, publication…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…As the present study identified a low variability of IL-17F at position +7488C/T (similarly as other studies in other populations: http://www.snpedia.com/index.php/Rs763780 ), the TT genotype occurred in 93.7%, and no CC homozygote was detected, we investigated this polymorphism only in a subgroup of 190 subjects. Further, no associations of this polymorphism with aggressive periodontitis (AgP) or CP [ 31 33 ] have been previously found. In contrast, the IL-17A −197A/G SNP was analyzed in the whole set of our 523 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the important role of IL-17 cytokine in T1DM and CP pathogenesis, no study has investigated IL-17 gene variability in T1DM patients so far and only a few studies have reported a relationship between polymorphisms in the IL-17 gene and periodontitis with contradictory results [ 29 33 ]. Therefore, in the present study, we aimed to investigate the association of IL-17A −197A/G (rs2275913) and IL-17F +7488C/T (His161Arg, rs763780) gene polymorphisms with T1DM and/or CP.…”
Section: Introductionmentioning
confidence: 99%